Neonatal Neurodegeneration in Alzheimer’s Disease Transgenic Mouse Model - Mazi, Aise Rumeysa (J Alzheimers Dis Rep, 2018)
Alzheimer’s disease (AD) is a progressive disorder characterized by a variety of molecular pathologies causing cortical dementia with a prominent memory deficit. Formation of the pathology, which begins decades before the diagnosis of the disease, is highly correlated with the clinical symptoms. Several proteomics studies were performed using animal models to monitor the alterations of the brain tissue proteome at different stages of AD. However, proteome changes in the brain regions of newborn transgenic mouse model have not been investigated yet. To this end, we analyzed protein expression alterations in cortex, hippocampus and cerebellum of transgenic mice carrying five familial AD mutations (5XFAD) at neonatal day-1. Our results indicate a remarkable difference in protein expression profile of newborn 5XFAD brain with region specific variations. Additionally, the proteins, which show similar expression alteration pattern in postmortem human AD brains, were determined. Bioinformatics analysis showed that the molecular alterations were mostly related to the cell morphology, cellular assembly and organization, and neuroinflammation. Moreover, morphological analysis revealed that there is an increase in neurite number of 5XFAD mouse neurons in vitro. We suggest that, molecular alterations in the AD brain exist even at birth, and perhaps the disease is silenced until older ages when the brain becomes vulnerable.